Corporate Culture and Ethical Leadership: Tone at the Top - Alfian Lutfi; Pasca Pratama; Muhamad Alfaris Siregar; Dzikri Syaeful Rahman; Ida Farida (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to examine the influence of Tone at the Top on company performance by using a literature review method as its analytical approach. Tone at the Top refers to the attitudes, policies, and values set by organizational leaders in fostering an ethical, transparent, and performance-oriented work culture. In this study, various sources from journals, books, and previous research are analyzed to identify the relationship between top-level leadership and operational effectiveness, employee productivity, as well as corporate sustainability. The literature review findings indicate that leaders who effectively implement a strong Tone at the Top tend to create a positive work environment, enhance employee engagement, and strengthen good corporate governance. Conversely, failure to establish a strong Tone at the Top can contribute to low employee morale, a higher risk of ethical violations, and weakened organizational performance.